2015
DOI: 10.1111/1750-3841.12771
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Lactic Acid Bacteria Isolated from Brazilian Water Buffalo Mozzarella Cheese

Abstract: The water buffalo mozzarella cheese is a typical Italian cheese which has been introduced in the thriving Brazilian market in the last 10 y, with good acceptance by its consumers. Lactic acid bacteria (LAB) play an important role in the technological and sensory quality of mozzarella cheese. In this study, the aim was to evaluate the diversity of the autochthones viable LAB isolated from water buffalo mozzarella cheese under storage. Samples were collected in 3 independent trials in a dairy industry located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…Zheng et al (2018b) observed that Streptococcus and Lactobacillus species were the primary strains in Kazak cheese. In buffalo mozzarella cheese, the main LABs were identified as Streptococcus thermophilus, Lactobacillus fermentum, Enterococcus faecium, Leuconostoc mesenteroides, Lactobacillus casei, Lactobacillus delbrueckii, Enterococcus durans, and Lactobacillus helveticus (Silva et al, 2015). In traditional yogurt, LAB strains consist of S. thermophilus, L. delbrueckii, L. mesenteroides, and Lactobacillus plantarum (İspirli and Dertli, 2018), whereas Lactobacillus, Lactococcus, and Streptococcus species are widespread in milk kefir (Rosa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al (2018b) observed that Streptococcus and Lactobacillus species were the primary strains in Kazak cheese. In buffalo mozzarella cheese, the main LABs were identified as Streptococcus thermophilus, Lactobacillus fermentum, Enterococcus faecium, Leuconostoc mesenteroides, Lactobacillus casei, Lactobacillus delbrueckii, Enterococcus durans, and Lactobacillus helveticus (Silva et al, 2015). In traditional yogurt, LAB strains consist of S. thermophilus, L. delbrueckii, L. mesenteroides, and Lactobacillus plantarum (İspirli and Dertli, 2018), whereas Lactobacillus, Lactococcus, and Streptococcus species are widespread in milk kefir (Rosa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Esses resultados foram similares aos de Silva, 27 que trabalhou com microbiota lática isolada de queijo Muçarela de búfala e observou que uma cultura mesófila de Lactobacillus também teve atividade proteolítica.…”
unclassified
“…Due to different methods applied, it is difficult to compare the obtained results with other studies. Nonetheless, referring to two recent papers describing the LAB diversity in artisanal buffalo's milk cheese (SILVA et al, 2015) and raw cow's milk cheese (DOMINGOS-LOPES et al, 2017) including MRS and M17 for isolation, a similar LAB microbiota was reported. Hence, lactobacilli (e.g.…”
Section: Identification Of Lab At Strain Levelmentioning
confidence: 76%